(untitled) (Research, Society and Development, 2020)
Humans can express very different therapeutic responses when the same drug is administered. However, the variations may be due to the phenotype, since differences in age, weight, gender, health and diet are among the important factors, but the genotype also contributes to the environment. However, the implementation of pharmacogenetic tests in clinical practice has been slow. There are still many barriers present that lead to its underutilization. The objective of present study is to present a systematic review of meta-analysis on personalized therapy in oncology, considering pharmacogenetics and current antineoplastic agents and as specific objectives: to discuss the development of pharmacogenomics in relation to antineoplastic agents. According to the search strategies, a total of 168 articles were found in the databases selected for the search, with 32 articles in the Pubmed database, 24 in the Lilacs database and 12 in the Scielo database. We conclude that the relationship to the pharmacokinetics and dynamics of drugs used in the treatment of different diseases, may be available in a large database. The benefits of pharmacogenetics range from choosing the drug that has the best therapeutic effects to increasing the effectiveness of clinical trials in discovering new drugs.